2013
DOI: 10.1111/add.12231
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use disorders and mortality: a systematic review and meta‐analysis

Abstract: Mortality in people with alcohol use disorders is markedly higher than thought previously. Women have generally higher mortality risks than men. Among all people with alcohol use disorders, people in younger age groups and people in treatment show substantially higher mortality risk than others in that group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
201
3
13

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(237 citation statements)
references
References 126 publications
20
201
3
13
Order By: Relevance
“…Por otro lado, el consumo exagerado de alcohol explicaría una parte importante de la mortalidad por lesiones no intencionadas (accidentes, ahogamiento, hipotermia, quemaduras), intencionadas (suicidio) u otras enfermedades graves que acarrean una elevada mortalidad durante el episodio agudo (Naimi et al, 2003). En todo caso, la mortalidad de pacientes con trastorno por uso de alcohol es elevada y puede llegar a ser hasta 20 veces superior a la de la población general de la misma edad (Fuster et al, 2015;Rivas et al, 2013;Roerecke y Rehm, 2013).…”
Section: Pacientes Con Trastorno Por Uso De Alcohol: Resultados Iniciunclassified
“…Por otro lado, el consumo exagerado de alcohol explicaría una parte importante de la mortalidad por lesiones no intencionadas (accidentes, ahogamiento, hipotermia, quemaduras), intencionadas (suicidio) u otras enfermedades graves que acarrean una elevada mortalidad durante el episodio agudo (Naimi et al, 2003). En todo caso, la mortalidad de pacientes con trastorno por uso de alcohol es elevada y puede llegar a ser hasta 20 veces superior a la de la población general de la misma edad (Fuster et al, 2015;Rivas et al, 2013;Roerecke y Rehm, 2013).…”
Section: Pacientes Con Trastorno Por Uso De Alcohol: Resultados Iniciunclassified
“…Given the associated increased morbidity, alcohol problems represent a major economic burden for society (Rehm et al 2009;Roerecke and Rehm 2013). The Alcohol in Europe Report estimated that the direct costs associated with alcohol accounted for 1.3% of the European gross domestic product (GDP), while the indirect costs, such as loss of working-life years, are twice that (Anderson 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Schutte et al (2003) found that, among older former problem drinkers (ages 55-65), mortality was 1.6 times higher than among lifetime non-problem drinkers. Roerecke and Rehm (2013) conducted a meta-analysis on drinking status and ischemic heart disease mortality and found significantly elevated mortality among former drinkers compared with long-term abstainers. Mertens et al (1996) reported that former drinkers often had a current illness, higher stress, lower friendship support, and an avoidant coping style.…”
mentioning
confidence: 99%